Predictive Factors for Plate Failure After Humeral Fracture Fixation: A Two-Trauma Center Study - Nino Nasution; Alif Aditya Nasution; Adrian Joshua Velaro; Bagas Tobing; Benny Hosiana Putra; Muhammad Morteza; Sayyid Muhammad Zidane; Habib Al Kahfi Nasution; Maksum Pandelima ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2026)
Background: Plate fixation is commonly used for humeral fractures, yet plate failure remains a serious complication that can delay union and impair function. This study aimed to identify factors associated with humeral plate failure in two trauma centers.Methods: A retrospective review of electronic medical records from two trauma centers in Medan, Indonesia was performed. Extracted variables included patient demographics, fracture location and pattern, plate type and material, time to clinical union, smoking status, and neurovascular complications. Comparative analyses between failure and non-failure groups were conducted using independent t-tests or Mann–Whitney tests for numerical variables and chi-square or Fisher’s exact tests for categorical variables. Statistical significance was set at p < 0.05.Results: Thirty-one patients were included, and 5 (16.1%) experienced plate failure. No significant differences were found for sex (p = 0.231), age (p = 0.614), or body mass index (p = 0.379). Plate failure was not significantly associated with fracture location (p = 0.175), fracture pattern (p = 1.000), plate material (p = 1.000), time to clinical union (p = 0.525), or plate type (p = 0.700). Smoking (p = 0.020) and neurovascular damage were significantly associated with plate failure (p = 0.008).Conclusions: In this cohort, smoking and neurovascular injury were significantly associated with an increased risk of humeral plate failure. Perioperative identification and management of neurovascular compromise, along with smoking cessation strategies, may reduce the risk of implant failure. Further studies with larger samples are warranted.